O discurso do professor de língua inglesa sobre docência na era digital - Daróz, Elaine Pereira (2012)
In technological society, we are often driven to use new technologies, since they are increasingly present in our daily lives. Education does not deprive this notice and, accordingly, has been mobilized. In public schools, the distribution of laptops to teachers, as well as tablets for students, the creation of computer labs and availability of multimedia features, such as data-show, the schools are examples of this notice of the government the use of technologies in teaching practice. However, what is the position of the teacher in this new scenario? This paper aims to analyze the speech of English teacher about teaching in the digital age. Under the focus of qualitative research, the work is guided on theoretical assumptions of Discourse Analysis of French line, founded by Michel Pêcheux, and developed by his followers in Brazil. Analytical procedures occurred from parts of the recordings, in consideration of the effect of a speech senses, and also in the design of a heterogeneous subject, subjugated by language, history and ideology, which makes his speech from different positions it occupies. This research aims to understand the position-subject English teacher in technological society as an essential, intrinsic to the teaching-learning process, and not just a vehicle for the transmission of knowledge.